The evolution and democratization of modern fashion: from Frederick Worth to Karl Lagerfeld's fast fashion - António Machuco Rosa (2013)
This article examines how the haute couture associated with fashion evolved from the ini-tial creation of Frederik Worth to Karl Lagerfeld. The main idea is to see how the manifestations of the desire to display himself are grounded on differentiation strategies that are always positioned themselves as an anti-fashion critic of previous fashions. In particular, it will be analyzed three moments in the process of democratization of fashion: the chic haute couture created by Coco Chanel in opposition to Paul Poiret conspicuous and ostentatious fashion, the Yves Saint Laurent strategy that indiferentiates gender, and the fast-fashion strategy developed by Karl Lagerfeld in his collection for H & M. From these three cases, and based on theories Thornstein Veblen and George Simmel, it will be presented a theoretical model that allows us to understand the overall dynamics of fashion change